Wave transmission of submerged breakwaters consisting multiple pipes - Manoharan, L.S. (Asian Research Publishing Network, 2017)
Various breakwaters have been developed to protect coastal areas from the force of waves. The majority of the breakwaters are gravity-type structures withstanding the wave energy by their effective masses. The construction of these gigantic structures is costly and the use of materials is substantial. This research study attempted to cope with the aforementioned problems by investigating wave attenuation performance of five submerged breakwaters that were made of multiple pipes in different configurations by the means of physical modelling. A series of experiments were conducted in a wave flume to study the wave transmission characteristics of the submerged breakwaters of different designs under regular waves. Wave attenuation efficiency of the breakwaters were expressed in terms of wave transmission coefficient Ct. The relationships between Ct and wave steepness Hi/L, relative breakwater width B/L and relative breakwater draft h/d were ascertained through a systematic experimental programme. The experimental results showed that the alternatively submerged breakwaters were better wave attenuator compared to the submerged ones, and the sloping front face of breakwaters helped in promoting wave breaking and energy dissipation. © 2006-2017 Asian Research Publishing Network (ARPN).